Antimicrobial Activity and Biological Compatibility Study of Methanolic Crude Extract of Senna auriculata (Flower) - Rahman Ahamed Fahmeedha Kansul; Venkatesan Santhosh; Alex Arockia; Brahma Neha (Wolters Kluwer Medknow Publications, 2024)
Senna auriculata is a little flowering tree or shrub that is indigenous to India and Sri Lanka. It is also known by the names Tanner's Cassia and Avarampoo. It is a member of the Fabaceae family and is popular for its therapeutic and beautifying effects. S. auriculata is used in traditional medicine to treat a wide range of conditions, including diabetes, fever, inflammation, skin problems, and liver issues. However, the antimicrobial activity of different species of S. auriculata from Tamil Nadu is still not fully explored. In this present study, the antimicrobial activity of S. auriculata (Flower) was obtained and shade dried and extracted the crude metabolites the, extracted metabolites was screened for it's antimicrobial properties and biological compatibility. The antimicrobial activity of crude metabolites shows 14 mm zone of inhibition (ZOI) for S. aureus at 2 mg/well, whereas the P. aeruginosa and C. albicans show 12 mm ZOI for at 2 mg/well concentration. The minimum inhibitory concentration also shows the 128 μg/mL for S. aureus and 256 μg/mL P. aeruginosa and E. faecalis. The biological compatibility of crude metabolites shows 5% of hemolytic activity at higher concentrations the compound the metabolites having S. auriculata (Flower) may be biologically compatible.